STRATEGI PEMASARAN DALAM PENINGKATAN CALON JAMAAH UMRAH (Studi Kasus AQM Tour and Travel Kota Bengkulu) - Putra, Fadilah Dwi; Mursalin, Supardi; Stiawan, Evan (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this writing is to find out how marketing strategies can increase the number of Umrah pilgrims at AQM Tour and Travel, Bengkulu city. To find out this, researchers used qualitative descriptive methods with data collection techniques and used observation, interview and documentation methods. From the research results, the marketing strategy for increasing the number of prospective Umrah pilgrims at AQM Tour and Travel in the city of Bengkulu is quite good and professional, starting from product planning, pricing, strategic locations and ways to promote products to prospective pilgrims. The strategy used by PT. AQM Tour and Travel Bengkulu City in marketing is the reference strategy or Marketing Mix (marketing mix). This strategy is part of a marketing strategy that follows theory and functions as a guide in using marketing elements that can be controlled by company leaders to achieve company goals in the field of marketing in AQM Tour and Travel, Bengkulu city.